Faktor Pendukung dan Penghambat dalam Pengarsipan Data pada Aplikasi Sistem Informasi Penelusuran Perkara (SIPP) di Pengadilan Militer 1-03 Padang - Saskia Paramita, Meldhi; Eriyanti, Fitri (Policy, Law and Political Research Center, 2023)
This research was conducted with the aim of analyzing the supporting and inhibiting factors in archiving data on the SIPP application at the Military Court 1-03 Padang. This study used a qualitative research type with a descriptive method with a total of 6 (six) informants. Test the validity of the data in this study using triangulation techniques and data sources. Data analysis techniques use qualitative methods. The results of this study are the supporting and inhibiting factors in archiving case data in the SIPP application. The findings of this study indicate that the supporting factors in archiving case data in the SIPP application are the use of hard disks, database backups. While the inhibiting factors for the SIPP application were the SIPP application which experienced trouble, maintenance on the SIPP application and 41.7% of the employees of the Military Court 1-03 Padang did not understand the use of the SIPP application.